Persistent inequalities in consultation incidence and prevalence of low back pain and osteoarthritis in England between 2004 and 2019. Issue 1 (2nd December 2022) - Yu, Dahai; Jordan, Kelvin P; Wilkie, Ross; Bailey, James; Fitzpatrick, Justine; Ali, Nuzhat; Niblett, Paul; Peat, George
Abstract: Objective: We wanted to determine whether socioeconomic inequalities in primary care consultation rates for two major, disabling musculoskeletal conditions in England narrowed or widened between 2004 and 2019. Methods: We analysed data from Clinical Practice Research Datalink Aurum, a national general practice electronic health records database, linked to national deprivation ranking of each patient's registered residential postcode. For each year, we estimated the age- and sex-standardized consultation incidence and prevalence for low back pain and OA for the most deprived 10% of neighbourhoods through to the least deprived 10%. We then calculated the slope index of inequality and relative index of inequality overall and by sex, age group and geographical region. Results: Inequalities in low back pain incidence and prevalence over socioeconomic status widened between 2004 and 2013 and stabilized between 2014 and 2019. Inequalities in OA incidence remained stable over socioeconomic status within the study period, whereas inequalities in OA prevalence widened markedly over socioeconomic status between 2004 and 2019. The widest gap in low back pain incidence and prevalence over socioeconomic status was observed in populations resident in northern English regions and London and in those of working age, peaking at 45–54 years. Conclusion: We found persistent, and generally increasing, socioeconomic inequalities in the rate of adults presenting to primary care in England with low back pain and OA between 2004 and 2019. Lay Summary: What does this mean for patients? Our study describes the extent of social inequalities in how many adults present to primary care with a painful musculoskeletal condition. We focused on two of the most common, disabling conditions: back pain and osteoarthritis. We analysed information from primary care electronic medical records across England. People living in the most deprived (poorest) neighbourhoods were more likely to seek the help of primary care than people of the same age and sex who lived in the least deprived (richest) neighbourhoods. Compared with general practices serving the richest neighbourhoods, a general practice serving the poorest neighbourhoods in England could see 15–40% more patients presenting with a new episode of back pain or osteoarthritis each year. These differences in rates between rich and poor were particularly noticeable among women, among working-age adults and in the north of England and London. Inequalities did not appear to have reduced between 2004 and 2019. Our study did not investigate underlying causes. However, it does highlight issues around workload and resourcing of general practices and the need for earlier and sustained preventive actions focused on poorer communities across England.